Neurotensin and Adverse Cardiovascular Outcomes in Patients Undergoing Percutaneous Coronary Intervention - Tscharre, Maximilian; Farhan, Serdar; Freynhofer, Matthias K.; Leutner, Michael; Baumgartner-Parzer, Sabina; Tentzeris, Ioannis; Vogel, Birgit; Tinhofer, Florian; Rohla, Miklos; Weiss, Thomas W.; Huber, Kurt; Kautzky-Willer, Alexandra (Frontiers in Cardiovascular Medicine, 2022)
Background: Neurotensin is involved in fatty acid and glucose metabolism and promotes the development of obesity and diabetes. These associations appear to be more pronounced in women. We investigated the association of neurotensin with long-term major adverse cardiovascular events (MACE) in patients presenting with acute coronary syndrome (ACS) or chronic coronary syndrome (CCS) undergoing percutaneous coronary intervention (PCI). Methods: We included 452 consecutive patients (144 [31.9%] females) undergoing PCI for ACS or CCS. Plasma samples drawn after PCI were analysed for neurotensin with an enzyme-linked immunoassay. As primary endpoint, a composite of MACE including all-cause death, non-fatal myocardial infarction and non-fatal stroke during seven years of follow-up was investigated. As secondary endpoint, we investigated all-cause death. Results: Neurotensin levels did not differ between male and female patients (p=0.560). MACE occurred in 150 (33.2%) patients. Restricted cubic splines demonstrated a U-shaped association of log-transformed neurotensin with the primary and secondary endpoint. Therefore, we dichotomized our cohort according to tertiles of log-transformed neurotensin. In Kaplan-Meier analysis including the total cohort and restricted to male patients log- neurotensin tertiles were not associated with MACE (both p>0.05). Moreover, in the overall cohort and in male patients multivariable Cox regression analysis log-neurotensin tertiles were not associated with MACE or with all-cause death (all p>0.05). However, in female patients log- neurotensin were associated with MACE in Kaplan-Meier analysis (log-rank p=0.013). Also, after multivariable adjustment female patients in the first tertile had a significantly increased risk for MACE compared to female patients in the second tertile (HR 3.84 [95% CI 1.71-8.60], p=0.001). There was tendency for increased risk in female patients in the third tertile compared to the second tertile (HR 2.14 [95% CI 0.97-4.73], p=0.058). Moreover, in female patients the first and the third tertile of log- neurotensin were associated with all-cause death (1st vs. 2nd tertile: HR 3.03 [95% CI 1.21-7.63], p=0.018; 3rd vs. 2nd tertile: HR 3.01 (95% CI 1.22- 7.44], p=0.016). Conclusion: In female patients with CAD undergoing PCI, neurotensin has a U-shaped relationship with adverse outcomes. These data suggest a sex specific association between neurotensin and long-term adverse events after PCI.